2015
DOI: 10.1097/nan.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Drug Shortages and Patient Safety

Abstract: Drug shortages present a growing problem in the United States, with the majority of shortages occurring among sterile injectable medications. Although the impact of shortages has been shown to adversely affect patient care in a variety of settings, those who are dependent on outpatient or home infusion therapy are especially vulnerable. Legislative action and the efforts of the U.S. Food and Drug Administration have helped reduce the occurrence of new shortages; however, the problem is not likely to be elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The characteristics of drug shortages, such as the assortment or range of non-available products, are different in each country but there are some common themes. In the USA, the majority of shortages were reported to occur among sterile injectable medications (McLaughlin and Skoglund, 2015 ). In addition, the number of generic medicines experiencing shortages in the USA has risen appreciably in recent years from 154 in 2007 to 456 in 2012 (United States Government Accountability Office Report, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of drug shortages, such as the assortment or range of non-available products, are different in each country but there are some common themes. In the USA, the majority of shortages were reported to occur among sterile injectable medications (McLaughlin and Skoglund, 2015 ). In addition, the number of generic medicines experiencing shortages in the USA has risen appreciably in recent years from 154 in 2007 to 456 in 2012 (United States Government Accountability Office Report, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The United States (US) is the country with more publications in the field (26 references) than many other countries. Many of these publications describe the professionals’ perspective of the situation at the health care jurisdictional level (Morrison, 2011; Golembiewski, 2012; Griffith et al, 2012; Becker et al, 2013; McKeever et al, 2013; McLaughlin et al, 2013; Bible et al, 2014; Goldsack et al, 2014; Butterfield et al, 2015; Caulder et al, 2015; McLaughlin and Skoglund, 2015; Gabrielli et al, 2016; Parsons et al, 2016; Setayesh and Mackey, 2016; Bocquet et al, 2017; Fox and Tyler, 2017; Mazer-Amirshahi et al, 2017; Rinaldi et al, 2017; Schwartzberg et al, 2017). Another study performed a comparison of medicines shortages between two hospital settings, one from Arabia Saudi and the other from the US (Alsheikh et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Published studies in hospitals allow a better follow up of the health consequences of medicine shortages (Pauwels et al, 2015; de Weerdt et al, 2017); which is more difficult in ambulatory care (Golembiewski, 2012; Becker et al, 2013; Goldsack et al, 2014; Jagsi et al, 2014; Chen et al, 2016). This scoping review identified a number of published articles describing inpatient challenges regarding medicine shortages in the US (Morrison, 2011; Golembiewski, 2012; Griffith et al, 2012; Becker et al, 2013; McKeever et al, 2013; McLaughlin et al, 2013; Bible et al, 2014; Goldsack et al, 2014; Butterfield et al, 2015; Caulder et al, 2015; McLaughlin and Skoglund, 2015; Gabrielli et al, 2016; Parsons et al, 2016; Setayesh and Mackey, 2016; Bocquet et al, 2017; Fox and Tyler, 2017; Mazer-Amirshahi et al, 2017; Rinaldi et al, 2017; Schwartzberg et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also identified information flow as an essential focus area in managing DCs owing to drug shortage. 3,4,14,17 However, timely communication and ensuring that messages about DCs reach everyone is difficult and can be extremely time consuming. 4,17 The pharmacy personnel in the focus group interviews acknowledged this.…”
Section: Discussionmentioning
confidence: 99%